A cluster of two psittacosis cases among women farmers exposed to Chlamydia psittaci‐infected domestic poultry in Zhejiang Province, China. (31st October 2022) - Liu, Shelan; Yang, Yong; Pang, Zhifeng; Liu, Ying; Li, Huan; Cai, Jian; Wu, Zhuoying; Luo, Yan; Tang, Yuhuan; Ying, Lihong; Qin, Shuwen; Miao, Ziping; et al.
Abstract: A cluster of Chlamydia psittaci ( C. psittaci ) cases was reported in Zhejiang Province, China, 2019. This study evaluates the extent of the outbreak and determines the source of infection. Real‐time PCR and sequencing of the ompA gene of C. psittaci were performed to identify the cases, the domesticated poultry and close contacts. The index patient was a 76‐year‐old woman with chronic vertigo, and Case 2 was a 64‐year‐old female farmer with herpes zoster. Both women bought psittaci ‐infected chickens or ducks from the same mobile street vendor and raised them for 10 days and 23 days before fever onset. There were no direct contact between the two women. C. psittaci test was positive for the two patients, one sick chicken, three healthy ducks and the vendor's chicken cage. Phylogenetic analysis showed that all seven C. psittaci positive samples carried identical ompA genotype A of C. psittaci . Of all of the patients' 148 close contacts, none tested positive for C. psittaci, or developed acute respiratory symptoms. Both patients were discharged after a 4‐week hospital stay. In conclusion, the source of this cluster was the poultry infected with C. psittaci, which occasionally cause infections in farmers, but inter‐human transmission seems unlikely.